Comparison of gaze behaviour of trainee and experienced surgeons during laparoscopic gastric bypass. Issue 3 (28th November 2017) - Erridge, S; Ashraf, H; Purkayastha, S; Darzi, A; Sodergren, M H
Abstract: Background: Eye tracking presents a novel tool that could be used to profile skill levels in surgery objectively. The primary aim of this study was to identify differences in gaze behaviour between expert and junior surgeons performing a laparoscopic Roux-en-Y gastric bypass (LRYGB) for obesity. Methods: This prospective observational study used a lightweight eye-tracking apparatus to determine the difference in gaze behaviours between expert (more than 75 procedures) and junior (75 or fewer procedures) surgeons at defined stages of LRYGB. Primary endpoints were normalized dwell time and fixation frequency. Secondary endpoints were blink rate, maximum pupil size and rate of pupil change. Results: A total of 20 procedures (12 junior, 8 expert) were analysed. Compared with juniors, experts showed a prolonged dwell time on the screen during angle of His dissection (median (range) 91·20 (83·40–94·40) versus 68·95 (59·80–87·60) per cent; P = 0·001), formation of the retrogastric tunnel (91·50 (85·80–95·50) versus 73·60 (34·60–90·50) per cent; P = 0·001) and gastric pouch formation (86·95 (83·60–90·20) versus 67·60 (37·10–80·00) per cent P < 0·001). Juniors had a greater blink frequency throughout all recorded segments ( P < 0·010) and had a larger maximum pupil size during all recorded operative segments ( P < 0·010). Rate of pupil change was greater in juniors in all analysed segments ( P < 0·010). Conclusion: These results suggest that experts display more focused attention on significant stimuli, alongside experiencing a reduced mental workload and having increased concentration. This has the potential for future use in validation of surgical skill in high-stakes assessment. Abstract : Potential uses in training and assessment